Kaidah Fiqhiyyah Terkait Syirkah dan Investasi - Ikhsan, Muhammad Miftahul; Meiriyanti, Deffa (Lembaga Yasin AlSys, 2024)
Islam has experienced the growth and development of the times, now it has reached the economy of contemporary Islam, with various renewable problems. Qawa'id Fiqhiyyah, qawa'id is carried out as a form of renewal of islamic economic problems, qawa'id fiqhiyyah provides practical guidelines derived from the Qur'an and Hadith that can be applied in society. This type of research uses literature research that takes data through information by obtaining library materials, data collection techniques for this research using documentation. data that has been obtained by reviewing and analyzing, both in the form of books, journals, research results. As well as by using descriptive analysis techniques. The principle of Murofiq tijari (trading facility) in Islam explains that there is freedom in the contract of transactions. The rule discussed is Al Ashlu Fil Musyarokati Wal Istitsmaroti Al Ibahatu. has two discussions, namely association and investment. then syirkah in the explanation is allowed if it is in accordance with the conditions, agreement of the parties, and does not carry out cooperation that is prohibited or makruh to be done. In investment, it is allowed under the applicable conditions, namely the rules that are carried out both in syirkah there must be agreement from the parties, move independently that realize the agreement together, and investments that must pay attention to the objectives of wanting to have an impact on positive and negative things that can benefit the community or can be detrimental.